2020
DOI: 10.9734/ajee/2020/v12i130148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physicochemical and Microbiological Characteristics of Water Samples of Okomu National Park, Edo State, Nigeria

Abstract: Water is very crucial for the survival and maintenance of most living organisms. The quality of water available for plant, animal or human use cannot therefore be compromised. This study therefore examined the physicochemical and microbiological characteristics of water samples in Okomu National Park, Edo State, Nigeria. Water samples were collected from four waterholes (three rivers and one stream) for two seasons (dry and wet) using grab sampling technique. These water samples were analysed for physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…observed in the study are of ecological health importance. Omonona et al [19] also reported similar findings in their study. Furthermore, Salmonella / Shigella (enteric pathogens) and Staphylococcus aureus, are seen as important indicators of the health of aquatic ecosystems [21] were observed in the water samples.…”
Section: Microbiological Characteristicssupporting
confidence: 81%
See 3 more Smart Citations
“…observed in the study are of ecological health importance. Omonona et al [19] also reported similar findings in their study. Furthermore, Salmonella / Shigella (enteric pathogens) and Staphylococcus aureus, are seen as important indicators of the health of aquatic ecosystems [21] were observed in the water samples.…”
Section: Microbiological Characteristicssupporting
confidence: 81%
“…Ajibade et al [22] had also reported similar findings in Kainji Lake National Park in Nigeria. Adetuga et al (2019b) and Omonona et al [19] also reported similar findings and attributed the probable cause to more contact from animals while drinking. Coliforms generally are important among bacterial indicators that are used in water quality monitoring and assessment [23].…”
Section: Microbiological Characteristicsmentioning
confidence: 58%
See 2 more Smart Citations
“…Notable antimicrobials that have been isolated (from where antibiotics originate) include filamentous ascomycetes (Aspergillus niger), commonly employed for citric acid production, 4 Streptomycetes, 5,6, Actinomycetes 6,7 and Bacillus. 6,8 Some of these antimicrobials are isolated and characterized from various sources; like fish spleen, 9,10 human skin, 11,12 plants/vegetable, 10,[13][14][15] water, 16 dumpsites, 10,17 industrial waste 18 and soil. 19,20 In a similar way, records of the isolation of fungi from various type of soils abounds.…”
Section: Introductionmentioning
confidence: 99%